Hepatitis D virus (HDV) prevalence in Austria is low but causes considerable morbidity due to fast progression to cirrhosis. Issue 10 (7th December 2021) - Jachs, Mathias; Binter, Teresa; Schmidbauer, Caroline; Hartl, Lukas; Strasser, Michael; Laferl, Hermann; Hametner‐Schreil, Stephanie; Lindorfer, Alexander; Dax, Kristina; Stauber, Rudolf E.; Kessler, Harald H.; Bernhofer, Sebastian; et al.
Abstract: Background: Hepatitis D virus (HDV) coinfection aggravates the course of hepatitis B virus (HBV). The prevalence of HDV in Austria is unknown. Objective: This national study aimed at (i) recording the prevalence of HDV‐infection in Austria and (ii) characterizing the "active" HDV cohort in Austria. Methods: A total of 10 hepatitis treatment centers in Austria participated in this multicenter study and retrospectively collected their HDV patients between Q1/2010 and Q4/2020. Positive anti‐HDV and/or HDV‐RNA‐polymerase chain reaction (PCR) results were retrieved from local database queries. Disease severity was assessed by individual chart review. Viremic HDV patients with clinical visits in/after Q1/2019 were considered as the "active" HDV cohort. Results: A total of 347 anti‐HDV positive patients were identified. In 202 (58.2%) patients, HDV‐RNA‐PCR test was performed, and 126/202 (62.4%) had confirmed viremia. Hepatocellular carcinoma was diagnosed in 7 (5.6%) patients, 7 (5.6%) patients underwent liver transplantation, and 11 (8.7%) patients died during follow‐up. The "active" Austrian HDV cohort included 74 (58.7%) patients: Evidence for advanced chronic liver disease (ACLD, i.e., histological F3/F4 fibrosis, liver stiffness ≥10 kPa, varices, or hepatic venous pressure gradient ≥6 mmHg) was detected in 38 (51.4%) patients, including 2 (5.3%) with decompensation (ascites/hepatic encephalopathy). About 37 (50.0%) patients of the "active" HDV cohort had previously received interferon treatment. Treatment with the sodium‐taurocholate cotransporting polypeptide inhibitor bulevirtide was initiated in 20 (27.0%) patients. Conclusion: The number of confirmed HDV viremic cases in Austria is low (<1% of HBV patients) but potentially underestimated. Testing all HBV patients will increase the diagnostic yield. More than half of viremic HDV patients had ACLD. Improved HDV testing and workup strategies will facilitate access to novel antiviral therapies.